2022
DOI: 10.3389/fmicb.2022.1001454
|View full text |Cite
|
Sign up to set email alerts
|

Insight into aphid mediated Potato Virus Y transmission: A molecular to bioinformatics prospective

Abstract: Potato, the world's most popular crop is reported to provide a food source for nearly a billion people. It is prone to a number of biotic stressors that affect yield and quality, out of which Potato Virus Y (PVY) occupies the top position. PVY can be transmitted mechanically and by sap-feeding aphid vectors. The application of insecticide causes an increase in the resistant vector population along with detrimental effects on the environment; genetic resistance and vector-virus control are the two core componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 191 publications
0
4
0
Order By: Relevance
“…Tanmaya Kumar Bhoi 1 † , Ipsita Samal 2 † , Deepak Kumar Mahanta 3 , J. Komal 4 , Mudasser Ahmed Khan 5 *Address all correspondence to: hanumaniasbhu@gmail.com † These authors contributed equally to this work, and all should be considered as co-first authors.…”
Section: Author Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanmaya Kumar Bhoi 1 † , Ipsita Samal 2 † , Deepak Kumar Mahanta 3 , J. Komal 4 , Mudasser Ahmed Khan 5 *Address all correspondence to: hanumaniasbhu@gmail.com † These authors contributed equally to this work, and all should be considered as co-first authors.…”
Section: Author Detailsmentioning
confidence: 99%
“…Soil health stands as the bedrock of terrestrial ecosystems, serving as a vital foundation for agricultural productivity, ecological stability, and the sustenance of diverse life forms [1]. Within this intricate web of soil dynamics, the role of soildwelling insects emerges as an integral component, orchestrating a delicate balance in the ecosystem [2][3][4]. In recent years, the integration of biochar as a soil amendment has garnered considerable attention for its potential to revolutionize soil health and agricultural sustainability [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the symptomatic samples that were taken to laboratory were infected with viruses. The population of aphids, the insect vector of both PVY and SLV (Bhoi et al, 2022;Lou et al, 2023), was observed to be low, likely due to routine insecticide application. The two viruses are also transmitted through vegetative propagation, the main means of potato and shallot transplantation.…”
Section: Rt-pcr and Virus Species Determinationmentioning
confidence: 99%
“…The two viruses are also transmitted through vegetative propagation, the main means of potato and shallot transplantation. While SLV is mostly confined to Allium spp., PVY is spreadable among a wide host range (Mansouri et al, 2021;Bhoi et al, 2022). These showed that viral diseases are potentially still hindering crop production in the area.…”
Section: Rt-pcr and Virus Species Determinationmentioning
confidence: 99%
“…Due to the PLRV's high occurrence, it became an emerging disease in Pakistan (Batool et al, 2011). The 5 th most dangerous plant virus, PVY, belongs to the family Potyviridae and contains an economically vital group of plant viruses (Bhoi et al, 2022). Worldwide and in Pakistan damages are up to 85% when the crop is developed from infected tubers (Thomas-Sharma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%